Edukasi Dalam Meningkatkan Efesiensi Pembayaran Digital Dengan Metode Partisipatif Pada Kantin Universitas Islam Negeri Fatmawati Sukarno Bengkulu - Nurlara, Heni; Arisantika, Vioza Dwi; Apriani, Erni; Afrianty, Nonie; Arisandy, Yosy (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This education accompanies the implementation of a digital payment system in the UINFAS Bengkulu canteen through a participatory approach involving canteen business actors, campus financial managers, students, and staff to evaluate technical feasibility and operational risk mitigation strategies. The results of the education show that the digital payment system is able to increase transaction efficiency by up to 30% and reduce financial recording errors due to human error, but its implementation faces obstacles in the form of limited understanding of business actors' technology, dependence on internet connectivity, and potential misuse of user data. To overcome these challenges, assistance is provided through digital training, transaction simulations, and the preparation of basic security protocols, so that this education recommends increasing digital literacy of canteen managers and establishing a community-based monitoring system to encourage the sustainability and effectiveness of the digital payment system in the campus environment.